Worrying News for Brazilian Caatinga: Prevalence of Batrachochytrium dendrobatidis in Amphibians. (November 2019) - Benício, Ronildo A.; Carvalho, Tamilie; Barbosa, Maria D. R.; Costa, Janiella de M; da Silva, Felipe C. C.; Fonseca, Mariluce G.
The chytrid fungus Batrachochytrium dendrobatidis (Bd) has been linked to the declines of more than 500 amphibian species globally. In Brazil, Bd has been identified in several regions but predominantly in the Atlantic Forest. Data on the occurrence of this amphibian pathogen in northeastern Brazil are scarce, specifically from the Caatinga ecoregion, where there is only one study that reports Bd in the region. This study is the first to show a high prevalence of Bd in Caatinga's species and includes two new records of species infected by Bd: Rhinella granulosa and R. jimi . In addition, we discuss the possibility of amphibian with terrestrial habits serving as potential Bd reservoirs in semiarid climate regions.